(untitled) (Historia, 2021)
The history of the Afrikaner Broederbond (AB) is well documented. Its functioning is closely examined in the books by Ivor Wilkins and H. Strydom, and by J.H.P. Serfontein. In Hermann Giliomee’s recent work, the influence of the AB has also received attention. According to Giliomee it is a misconception, perpetuated by South African historiography, that the Broederbond’s influence was on a par with that of the NP. The Afrikaner Broederbond itself has also produced histories of the society, and in 2009, Rev Nico Smith published his inside perspective on the AB.